Distribution, Status, Potentiality and Maketing Importance of Guchchi Chyau (Morchella conica, pers.) in Mugu District, Nepal - Karki, Ajay (The Initiation, 2010)
Morchella conica, pers (Guchchi Chyau) is achlorophyllus but posh fungus species often called as morel mushroom. Its use is not only limited to the household sector but also used in food and non food industries. Distribution status and potentiality is discerned in this paper and is linked it up with the financial contribution made to enhance local livelihoods. The general morphology, ecology and distribution pattern is critically analyzed to link up its importance. It is distributed within twelve VDCs of Mugu district which keeps tremendous potentiality to address the problem of poverty in the region. Information of this research based article is collected from direct field observation, focus group discussion; key informants interview and surface analysis of market structure. Haphazard and immature collections are the issues regarding its sustainability Key Words: Collection, Storage, Value addition, Cultivation, Marketing DOI: 10.3126/init.v3i0.2500 The Initiation Vol.3 2009 p.97-101